Skin glands, poison and mimicry in dendrobatid and leptodactylid amphibians - Prates, Ivan; Antoniazzi, Marta M.; Sciani, Juliana M.; Pimenta, Daniel C.; Toledo, Luis Felipe; Haddad, Celio Fernando Baptista [UNESP]; Jared, Carlos (Wiley-Blackwell, 2012)
In amphibians, secretions of toxins from specialized skin poison glands play a central role in defense against predators. The production of toxic secretions is often associated with conspicuous color patterns that warn potential predators, as it is the case of many dendrobatid frogs, including Ameerega picta. This species resembles the presumably nontoxic Leptodactylus lineatus. This study tests for mimicry by studying the morphology and distribution of skin glands, components of skin secretion, and defensive behavior. Dorsal skin was studied histologically and histochemically, and skin secretions were submitted to sodium dodecyl sulfate polyacrylamide gel electrophoresis, reversed phase high performance liquid chromatography and assays for proteolytic activity. We found that poison glands in A. picta are filled with nonprotein granules that are rich in carbohydrates, while L. lineatus glands present protein granules. Accordingly, great amounts of proteins, at least some of them enzymes, were found in the poison of L. lineatus but not in that of A. picta. Both species differ greatly on profiles of gland distribution: In L. lineatus, poison glands are organized in clusters whose position coincides with colored elements of the dorsum. These regions are evidenced through a set of displays, suggesting that poison location is announced to predators through skin colors. In contrast, A. picta presents lower densities of glands, distributed homogeneously. This simpler profile suggests a rather qualitative than quantitative investment in chemical defense, in agreement with the high toxicity attributed to dendrobatids in general. Our data suggest that both species are toxic or unpalatable and transmit common warning signals to predators, which represents a case of Mullerian mimicry. J. Morphol. 2012. (C) 2011 Wiley Periodicals, Inc.
Keywords: amphibia; defensive behavior; skin morphology; poison glands; mimicry